2008
DOI: 10.1080/09064710701214346
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of potassium, magnesium, manganese and iron in relation to porosity of tilled and orchard loamy soil

Abstract: The aim of this study was to examine the leaching of potassium, magnesium, manganese and iron in tilled and orchard silty loam soil. The experimental treatments were: conventionally tilled field (CT) with main tillage operations including preplough (10 cm)'harrowing followed by mouldboard ploughing to 20 cm depth, and a 35-year-old apple orchard (OR) with a permanent sward. Leaching of the cations was determined in soil columns of undisturbed structure, 21.5 cm diameter and 20 cm height, from a depth of 0Á20 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Long-term annual mean temperature and precipitations at the site are 7.4°C and 572 mm, respectively. The experimental objects included: tilled field (100 x 150 m) with main tillage operations including pre-plough (0.1 m depth) + harrowing, mould-board ploughing (0.2 m depth) and crop rotation involving selected cereals, root crops and legume crops, and orchard 35 year-old apple orchard (100 x 200 m) with permanent sward that was mown in the interrows during the growing season (Lipiec et al, 2011;Siczek et al, 2008). The management practices on tilled were used for 30 years.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term annual mean temperature and precipitations at the site are 7.4°C and 572 mm, respectively. The experimental objects included: tilled field (100 x 150 m) with main tillage operations including pre-plough (0.1 m depth) + harrowing, mould-board ploughing (0.2 m depth) and crop rotation involving selected cereals, root crops and legume crops, and orchard 35 year-old apple orchard (100 x 200 m) with permanent sward that was mown in the interrows during the growing season (Lipiec et al, 2011;Siczek et al, 2008). The management practices on tilled were used for 30 years.…”
Section: Methodsmentioning
confidence: 99%
“…Change of land use from tilled to grass or no-till system leads further to a higher soil organic carbon content and modified soil acidity (Lipiec et al, 2011). The differences in aggregate and pore structure and soil chemistry affect pore water residence time and sorption capacity and thereby leaching kinetics of agricultural chemicals (Siczek et al, 2008).It was shown that the presence of macropores made by earthworms can lessen the potential for leaching of pesticides due to adsorption in organic burrow linings, and contribute to preferential flow and thereby permit solutes to bypass large parts of soil (Stehouwer et al, 1994). Moreover, earthworm feeding motion, due to ingesting and carrying herbicide residues away from the soil surface, can increase the amount of non-leachable herbicide residues in the soil (Farenhorst et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation coefficients between the Na + concentration and leaching ratios are 0.421, 0.897 and 0.957 in the first year and 0.936, 0.921 and 0.970 in the second year for S 1 , S 2 and S 3 , respectively. Related to the cation intercourse, Siczek et al (2008) reported that the leaching of cations is dependent on the concentrations of other cations in the soil solution. For example, Jalali & Rowell (2003) reported that the increase of potassium would result with the increase of Ca 2+ due to the ability of calcium ions.…”
Section: Smb For Cationsmentioning
confidence: 99%